Drug repurposing screen for the rare disease ataxia-telangiectasia - Namrata Jayanth; Gurvan Mahé; Matthew Campbell; Mike Lipkin; Shushant Jain; Rhea van de Bospoort; Jennifer Thornton; Brad Margus; David F. Fischer (SLAS Discovery)
Ataxia Telangiectasia (A-T) is a rare, autosomal recessive genetic disorder characterized by a variety of symptoms, including progressive neurodegeneration, telangiectasia, immunodeficiency, and an increased susceptibility to cancer. It is caused by bi-allelic mutations impacting a gene encoding a serine/threonine kinase ATM (Ataxia Telangiectasia Mutated), which plays a crucial role in DNA repair and maintenance of genomic stability. The disorder primarily affects the nervous system, leading to a range of neurological issues, including cerebellar ataxia. The cause of neurodegeneration due to mutations in ATM is still an area of investigation, and currently there is no known treatment to slow down or stop the progression of the neurological problems.In this collaboration of the A-T Children's Project (ATCP) with Charles River Discovery, we successfully developed a high-throughput assay using induced pluripotent stem cells (iPSC) from A-T donors to measure DNA damage response (DDR). By measuring the changes in levels of activated phosphorylated CHK2 (p-CHK2), which is a downstream signaling event of ATM, we were able to identify compounds that restore this response in the DDR pathway in A-T derived patient cells. Over 6,000 compounds from small molecule drug repurposing libraries were subsequently screened in the assay developed, leading to identification of several promising in vitro hits.Using the assay developed and the identified hits opens avenues to investigate potential therapeutics for A-T.